Binder composition for all-solid-state secondary batteries
The use of a specific polymer and antioxidant combination in the binder composition for all-solid-state secondary batteries addresses output and cycle characteristic issues, enhancing battery performance through improved dispersibility and adhesion, particularly in high-temperature conditions.
Patent Information
- Application Number
- JP2020563013
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-28
- Filing Date
- 2019-12-05
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2039-12-05
AI Technical Summary
Existing all-solid-state secondary batteries require improvements in output characteristics and high-temperature cycle characteristics, particularly for applications in electric vehicles and large-scale storage batteries, and current binder compositions impose implementation burdens or affect battery performance due to the use of specific polymers and antioxidants.
A binder composition for all-solid-state secondary batteries comprising a polymer with 25% to 95% (meth)acrylic acid ester monomer units and a gel content of 50% or less, combined with an antioxidant in the range of 0.005 to 0.5 parts by mass, enhances dispersibility and adhesion, reducing internal stress and improving cycle characteristics.
The proposed binder composition improves the output characteristics and high-temperature cycle characteristics of all-solid-state secondary batteries by enhancing dispersibility, adhesion, and reducing internal stress during manufacturing, leading to better battery performance.
Smart Images

Figure 0007654977000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder composition for an all-solid-state secondary battery, a slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, a slurry composition for an electrode of an all-solid-state secondary battery, a solid electrolyte layer for an all-solid-state secondary battery, an electrode for an all-solid-state secondary battery, and an all-solid-state secondary battery. [Background technology]
[0002] In recent years, the demand for secondary batteries such as lithium-ion secondary batteries has been increasing for various applications, including portable terminals such as portable information terminals and portable electronic devices, as well as small home power storage devices, motorcycles, electric vehicles, hybrid electric vehicles, etc. As the applications expand, further improvements in the safety of secondary batteries are required.
[0003] In view of this, as a secondary battery with high safety, attention has been focused on all-solid-state secondary batteries that use solid electrolytes instead of organic solvent electrolytes, which are highly flammable and have a high risk of ignition in the event of leakage.
[0004] Here, the all-solid-state secondary battery has a solid electrolyte layer between a positive electrode and a negative electrode. The electrodes (positive electrode, negative electrode) can be formed by applying a slurry composition containing an electrode active material (positive electrode active material, negative electrode active material), a binder, and a solid electrolyte onto a current collector, drying the composition, and providing an electrode mixture layer (positive electrode mixture layer, negative electrode mixture layer) on the current collector, and the solid electrolyte layer can be formed by applying a slurry composition containing a binder and a solid electrolyte onto an electrode or a release substrate, and drying the composition. The all-solid-state secondary battery is generally produced by stacking a positive electrode and a negative electrode so that the positive electrode mixture layer of the positive electrode and the negative electrode mixture layer of the negative electrode face each other via a solid electrolyte layer, and then by pressing.
[0005] Conventionally, attempts have been made to improve the performance of all-solid-state secondary batteries by improving the binder contained in a slurry composition for an electrode or a solid electrolyte layer. Patent Document 1 describes that the output characteristics and charge / discharge cycle characteristics of an all-solid-state secondary battery are improved by using a polymer having a particle structure and a water-soluble polymer in combination as a binder.
[0006] Patent Documents 2 and 3 describe that an increase in the interfacial resistance of a solid electrolyte layer can be suppressed without applying pressure by using a polymer having a hard segment and a soft segment selected from an amide bond, a urea bond, a urethane bond, and an imide bond as a binder.
[0007] Patent Document 4 describes that by using polyurethane, polyurea, polyamide, polyimide, and / or polyester as a binder and blending an antioxidant, it is possible to prevent oxidative deterioration of the solid electrolyte and the binder and suppress performance degradation during long-term use. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2017 / 47378 [Patent Document 2] International Publication No. 2015 / 46313 [Patent Document 3] JP 2015-88480 A [Patent Document 4] JP 2018-88306 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, Patent Documents 2 and 3 require the preparation of a specific polymer, which imposes a large burden on implementation, and Patent Document 4 further contains a large amount of an antioxidant in the binder to prevent oxidation, which raises concerns about the effect on the output characteristics, etc. of the all-solid-state secondary battery. On the other hand, the output characteristics and charge / discharge cycle characteristics that Patent Document 1 aims at are particularly noteworthy characteristics among the characteristics of all-solid-state secondary batteries that are expected to be applied to electric vehicles, large-scale storage batteries, and the like, and further improvement in the cycle characteristics in the high temperature range is required.
[0010] An object of the present invention is to provide a binder composition for an all-solid-state secondary battery, which can provide an all-solid-state secondary battery having excellent output characteristics and high-temperature cycle characteristics. [Means for solving the problem]
[0011] The present inventors have found that the above object can be achieved by using a specific polymer as a binder and combining it with a specific amount of an antioxidant in a binder composition for an all-solid-state secondary battery, and have completed the present invention.
[0012] That is, the present invention advantageously solves the above problems, A binder composition for an all-solid-state secondary battery, comprising a polymer, an antioxidant, and an organic solvent, The polymer contains 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units and has a gel content of 50% by mass or less, the amount of the antioxidant is 0.005 parts by mass or more and 0.5 parts by mass or less relative to 100 parts by mass of the polymer; The present invention relates to a binder composition for an all-solid-state secondary battery. A polymer containing 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units and having a gel content of 50% by mass or less is hereinafter also referred to as a "(meth)acrylic polymer", and an aging agent in an amount of 0.005 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the polymer is hereinafter also referred to as a "specific amount of antioxidant".
[0013] In this specification, the term "binder composition for an all-solid-state secondary battery" refers to a material for producing a slurry composition for an all-solid-state secondary battery (a slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, a slurry composition for an electrode of an all-solid-state secondary battery), and includes a binder and an organic solvent. The binder composition for an all-solid-state secondary battery of the present invention is characterized in that the binder is the above-mentioned (meth)acrylic polymer and contains a specific amount of an antioxidant.
[0014] The mechanism by which the binder composition for an all-solid-state secondary battery of the present invention provides an all-solid-state secondary battery with excellent output characteristics and high-temperature cycle characteristics is not clear, but can be presumed as follows. The binder composition for all-solid-state secondary batteries of the present invention imparts dispersibility to the slurry composition for solid electrolyte layer for all-solid-state secondary batteries and the slurry composition for electrodes for all-solid-state secondary batteries using the binder composition, mainly based on the (meth)acrylic polymer, and imparts plasticity to the layer formed using the slurry composition, mainly based on a specific amount of an antioxidant. Therefore, the leveling property during coating of the slurry composition is improved, and the adhesion of the layer formed after drying the slurry composition to the substrate is improved. This provides excellent output characteristics to the all-solid-state secondary battery. Here, the specific amount of the antiaging agent provides plasticity by improving the slippage between the components in the layer formed using the slurry composition, and by the same action, the specific amount of the antiaging agent reduces the internal stress of each layer when pressure is applied to each layer during the battery manufacturing process. This prevents the internal stress in each layer from becoming apparent and deteriorating the cycle characteristics when charge / discharge cycles are repeated, and improves the cycle characteristics of the all-solid-state secondary battery in the high temperature range.
[0015] As described above, by using the binder composition for all-solid-state secondary batteries of the present invention, the internal stress of each layer during press processing can be reduced. In addition, since the adhesion of the layer formed after drying the slurry composition is improved, it is possible to lower the pressure during press processing, relatively reduce the amount of binder, and relatively increase the amount of electrode active material and solid electrolyte. In this way, the binder composition for all-solid-state secondary batteries of the present invention is effective in improving battery performance (pressing property) on the premise of the production of all-solid-state secondary batteries by press processing.
[0016] In this specification, "(meth)acrylic" means "acrylic and / or methacrylic". In this specification, "monomer unit" means "structural unit derived from that monomer." Furthermore, "containing a monomer unit" means "a polymer obtained using that monomer contains a structural unit derived from the monomer," and the content of the monomer unit is expressed as a percentage relative to the entire polymer, which is taken as 100% by mass. In this specification, the "gel amount" can be measured by the method described in the Examples section of this specification.
[0017] In the binder composition for an all-solid-state secondary battery of the present invention, it is preferable that the polymer further contains an α,β-unsaturated nitrile monomer unit. By using a polymer further containing an α,β-unsaturated nitrile monomer unit as a binder, it is possible to impart better dispersibility to the slurry composition, thereby effectively improving the output characteristics. In the binder composition for an all-solid-state secondary battery of the present invention, it is more preferable to use a polymer containing α,β-unsaturated nitrile monomer units in an amount of 2% by mass or more and 30% by mass or less.
[0018] In the binder composition for all-solid-state secondary batteries of the present invention, it is preferable that the polymer further contains a hydrophobic monomer unit. In this specification, the term "hydrophobic monomer unit" means "a monomer unit other than a (meth)acrylic acid ester monomer unit and an α,β-unsaturated nitrile monomer unit, the solubility of which in water (25° C.) is 1 g / 1 L or less." By using a polymer further containing a hydrophobic monomer unit as a binder, it is possible to impart better dispersibility to the slurry composition, thereby effectively improving the output characteristics. In the binder composition for all-solid-state secondary batteries of the present invention, it is more preferable to use a polymer containing 3% by mass or more and 60% by mass or less of the hydrophobic monomer unit.
[0019] In the binder composition for an all-solid-state secondary battery of the present invention, the antioxidant is preferably at least one selected from the group consisting of phenol-based antioxidants and organic phosphorus-based antioxidants. By using these antioxidants, the pressing property can be effectively improved, and thus the high-temperature cycle properties can be further improved.
[0020] The present invention relates to a slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, comprising any one of the binder compositions for an all-solid-state secondary battery and a solid electrolyte. The slurry composition for a solid electrolyte of an all-solid-state secondary battery of the present invention has excellent dispersibility and pressability, and can provide excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0021] The present invention relates to a slurry composition for an all-solid-state secondary battery electrode, comprising any one of the binder compositions for an all-solid-state secondary battery described above, an electrode active material, and a solid electrolyte. The slurry composition for an all-solid-state secondary battery electrode of the present invention has excellent dispersibility and pressability, and can provide excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0022] The present invention relates to a solid electrolyte layer for an all-solid-state secondary battery formed using the above-mentioned slurry composition for a solid electrolyte layer for an all-solid-state secondary battery. The solid electrolyte layer for an all-solid-state secondary battery of the present invention can provide excellent output characteristics and high-temperature cycle characteristics in the all-solid-state secondary battery.
[0023] The present invention relates to an electrode for an all-solid-state secondary battery, comprising an electrode mixture layer formed using the above-mentioned slurry composition for an all-solid-state secondary battery. The electrode for an all-solid-state secondary battery of the present invention can provide excellent output characteristics and high-temperature cycle characteristics in an all-solid-state secondary battery.
[0024] The all-solid-state secondary battery of the present invention includes at least one of the solid electrolyte layer for an all-solid-state secondary battery and the electrode for an all-solid-state secondary battery, and has excellent output characteristics and high-temperature cycle characteristics. Effect of the Invention
[0025] According to the present invention, there is provided a binder composition for an all-solid-state secondary battery, which can provide an all-solid-state secondary battery having excellent output characteristics and cycle characteristics. Furthermore, according to the present invention, there are provided a slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, a slurry composition for an electrode of an all-solid-state secondary battery, a solid electrolyte layer for an all-solid-state secondary battery, and an electrode for an all-solid-state secondary battery, which can provide an all-solid-state secondary battery having excellent output characteristics and cycle characteristics. The all-solid-state secondary battery of the present invention has excellent output characteristics and high-temperature cycle characteristics and is highly industrially useful. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, an embodiment of the present invention will be described in detail. The binder composition for an all-solid-state secondary battery of the present invention is used as a material for producing a slurry composition for an all-solid-state secondary battery (a slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, a slurry composition for an electrode of an all-solid-state secondary battery). The slurry composition for a solid electrolyte layer of an all-solid-state secondary battery of the present invention is used when forming a solid electrolyte layer of an all-solid-state secondary battery, and the slurry composition for electrodes of an all-solid-state secondary battery of the present invention is used when forming an electrode mixture layer (positive electrode mixture layer, negative electrode mixture layer) of an all-solid-state secondary battery. The electrodes (positive electrode, negative electrode) for an all-solid-state secondary battery of the present invention include the above-mentioned electrode mixture layer (positive electrode mixture layer, negative electrode mixture layer). The all-solid-state secondary battery of the present invention comprises at least one of the solid electrolyte layer for an all-solid-state secondary battery of the present invention and the electrode for an all-solid-state secondary battery of the present invention.
[0027] (Binder composition for all-solid-state secondary batteries) The binder composition for an all-solid-state secondary battery of the present invention comprises a polymer, an antioxidant, and an organic solvent, wherein the polymer contains 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units, has a gel amount of 50% by mass or less, and the amount of the antioxidant per 100 parts by mass of the polymer is 0.005 parts by mass or more and 0.5 parts by mass or less.
[0028] <(Meth)acrylic polymer> In the present invention, the polymer ((meth)acrylic polymer) containing 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units and having a gel content of 50% by mass or less is a binder component. The binder component is a component that binds together components contained in a solid electrolyte layer or binds together components contained in an electrode mixture layer, and holds them so as not to be detached from the mixture layer. The (meth)acrylic polymer may be one type or a combination of two or more types in any ratio.
[0029] Examples of the (meth)acrylic acid ester monomer in the (meth)acrylic acid ester monomer unit include acrylic acid alkyl esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, stearyl acrylate, and 2-ethylhexyl acrylate; acrylic acid alkoxy esters such as 2-methoxyethyl acrylate and 2-ethoxyethyl acrylate; 2-(perfluoroalkyl)ethyl acrylates such as 2-(perfluorobutyl)ethyl acrylate and 2-(perfluoropentyl)ethyl acrylate; and methyl methacrylate. methacrylic acid alkyl esters such as ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, tridecyl methacrylate, n-tetradecyl methacrylate, stearyl methacrylate, and 2-ethylhexyl methacrylate; methacrylic acid alkoxy esters such as 2-methoxyethyl methacrylate and 2-ethoxyethyl methacrylate; 2-(perfluoroalkyl)ethyl methacrylates such as 2-(perfluorobutyl)ethyl methacrylate and 2-(perfluoropentyl)ethyl methacrylate; benzyl acrylate; and the like. The (meth)acrylic acid ester monomer also includes a diester of an α,β-ethylenically unsaturated dicarboxylic acid, and examples thereof include lower alkyl diesters of itaconic acid such as diethyl itaconate and dibutyl itaconate. Among these, methyl acrylate, ethyl acrylate, methyl methacrylate, 2-ethylhexyl acrylate, n-butyl acrylate, t-butyl acrylate, and dibutyl itaconate are preferred, and ethyl acrylate, n-butyl acrylate, and t-butyl acrylate are more preferred.These may be one type or a combination of two or more types in any ratio.
[0030] The content of the (meth)acrylic acid ester monomer unit in the (meth)acrylic polymer is 25% by mass or more and 95% by mass or less. In view of the fact that the dispersion state of the solid electrolyte and the like in the slurry composition using the binder composition is good, excellent leveling properties are obtained, and it is advantageous in improving the output characteristics, the content is preferably 28% by mass or more, more preferably 30% by mass or more, and even more preferably 32% by mass or more, and is also preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 83% by mass or less.
[0031] The gel content of the (meth)acrylic polymer is 50% by mass or less, more preferably 10% by mass or less, and particularly preferably 0%. If it is less than the upper limit, the binder composition is easily dissolved in an organic solvent, and a good dispersion state of the solid electrolyte and the like is easily obtained in the slurry composition. The gel content can be controlled by the type and amount of the monomer in the polymer, the type and amount of the chain transfer agent used during polymerization, the polymerization temperature, and the like.
[0032] It is important that the (meth)acrylic polymer in the present invention contains 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units and has a gel content of 50% by mass or less. As long as this requirement is satisfied, the type and content of monomer units other than the (meth)acrylic acid ester monomer units can be arbitrary.
[0033] The (meth)acrylic polymer preferably further contains an α,β-unsaturated nitrile monomer unit. Examples of the α,β-unsaturated nitrile monomer include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, and α-ethylacrylonitrile. Among these, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. The α,β-unsaturated nitrile monomer may be one type or a combination of two or more types in any ratio.
[0034] The content of the α,β-unsaturated nitrile monomer unit is preferably 2% by mass or more, more preferably 3% by mass or more, particularly preferably 4% by mass, and is preferably 30% by mass or less, more preferably 28% by mass or less, particularly preferably 26% by mass or less. If it is equal to or more than the lower limit, the dispersion state of the solid electrolyte and the like in the slurry composition using the binder composition can be further improved, and the output characteristics can be effectively improved. If it is equal to or less than the upper limit, it is advantageous in that the polymer is easily dissolved in an organic solvent.
[0035] The (meth)acrylic polymer may further contain a hydrophobic monomer unit. Examples of the hydrophobic monomer unit include an aromatic vinyl monomer unit, a conjugated diene monomer unit, and an olefin monomer unit. The hydrophobic monomer unit does not include a (meth)acrylic acid ester monomer unit or an α,β-unsaturated nitrile monomer. The hydrophobic monomer unit may be one type or a combination of two or more types in any ratio.
[0036] Examples of the aromatic vinyl monomer include aromatic vinyl monomers such as styrene, chlorostyrene, vinyltoluene, t-butylstyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, α-methylstyrene, and divinylbenzene. Among these, styrene and vinylnaphthalene are preferred. Examples of the conjugated diene monomer include conjugated diene compounds having 4 or more carbon atoms, such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, etc. Among these, 1,3-butadiene and isoprene are preferred. Examples of the olefin monomer include 1-olefin monomers, and examples of the 1-olefin include ethylene, propylene, and 1-butene, with ethylene being preferred. The olefin monomer unit may be a structural unit (conjugated diene hydride unit) obtained by hydrogenating a conjugated diene monomer unit, and among these, a 1,3-butadiene monomer unit, a 1,3-butadiene hydride unit, which is a structural unit obtained by hydrogenating an isoprene monomer unit, and an isoprene hydride unit are preferred.
[0037] The content of the hydrophobic monomer unit is preferably 3% by mass or more, more preferably 5% by mass or more, even more preferably 12% by mass or more, particularly preferably 14% by mass or more, and is preferably 60% by mass or less, more preferably 55% by mass or less, even more preferably 50% by mass or less, particularly preferably 45% by mass or less, from the viewpoint of imparting further dispersibility to the solid electrolyte and the like in the slurry composition and further improving the output characteristics. Also, if the upper and lower limits are within the above ranges, when the composition is used in a slurry composition for an all-solid-state secondary battery electrode, the dispersibility of the electrode active material and the conductive material can be easily improved.
[0038] The (meth)acrylic polymer may contain other monomer units other than the above-mentioned various monomer units. Examples of other monomer units include unsaturated carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, and fumaric acid; amide monomers such as acrylamide, N-methylolacrylamide, and acrylamido-2-methylpropanesulfonic acid; halogen atom-containing monomers such as vinyl chloride and vinylidene chloride; vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl butyrate, and vinyl benzoate; vinyl ether monomers such as methyl vinyl ether, ethyl vinyl ether, and butyl vinyl ether; vinyl ketone monomers such as methyl vinyl ketone, ethyl vinyl ketone, butyl vinyl ketone, hexyl vinyl ketone, and isopropenyl vinyl ketone; heterocyclic ring-containing vinyl monomers such as N-vinylpyrrolidone, vinylpyridine, and vinylimidazole; glycidyl group-containing monomers such as glycidyl acrylate, glycidyl methacrylate, and allyl glycidyl ether; and the like. These may be one or a combination of two or more in any ratio.
[0039] The (meth)acrylic polymer may be composed of 25% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units and one or more selected from α,β-unsaturated nitrile monomer units, hydrophobic monomer units, and other monomers. The suitable amounts and types of the α,β-unsaturated nitrile monomer units, hydrophobic monomer units, and other monomers are as described above.
[0040] The weight average molecular weight of the (meth)acrylic polymer is preferably 50,000 or more, more preferably 100,000 or more, from the viewpoint of slurry storage stability, and is preferably 5,000,000 or less, more preferably 2,000,000 or less, from the viewpoint of slurry dispersibility. In this specification, the "weight average molecular weight" can be measured by the method described in the Examples section of this specification.
[0041] The method for preparing the (meth)acrylic polymer is not particularly limited, and the (meth)acrylic polymer can be obtained by polymerizing a monomer composition containing the above-mentioned monomers. The content ratio of each monomer in the monomer composition can be determined based on the content ratio of each monomer unit in the polymer. The polymerization method is not particularly limited, and examples thereof include solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization. In each polymerization method, an emulsifier, a polymerization initiator, and the like can be used as necessary. The olefin monomer unit can be introduced by hydrogenating the conjugated diene monomer unit. The hydrogenation method is not particularly limited, and a known method can be used.
[0042] <Anti-aging agent> The binder composition for all-solid-state secondary batteries of the present invention contains an antiaging agent. The antiaging agent is not particularly limited, and examples thereof include phenolic antiaging agents, organophosphorus antiaging agents, amine antiaging agents, quinone antiaging agents, sulfur antiaging agents, and phenothiazine antiaging agents. In terms of obtaining better adhesion and effectively improving pressability, phenolic antiaging agents and organophosphorus antiaging agents are preferred, and phenolic antiaging agents and phosphite antiaging agents are more preferred. The antiaging agent may be one type or a combination of two or more types in any ratio. The antiaging agent preferably contains one or more types selected from phenolic antiaging agents and organophosphorus antiaging agents, and more preferably contains at least a phenolic antiaging agent.
[0043] Phenol-based antioxidants include 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butylphenol, butyl hydroxyanisole, 2,6-di-t-butyl-α-dimethylamino-p-cresol, octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (also known as octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate), styrenated phenol, 2,2'-methylene-bis(6-α-methyl-benzyl-p-cresol), 4,4'-methylenebis(2,6-di-t-butylphenol), 2,2'-methylene-bis(4-methyl-6-t-butylphenol), alkylated bisphenols, butylated reaction products of p-cresol and dicyclopentadiene, pentaerythritol tetrakis[3-( Sulfur-free phenolic antioxidants such as 3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,4,6-tris(3',5'-di-t-butyl-4'-hydroxybenzyl)mesitylene; 2,2'-thiobis-(4-methyl-6-t-butylphenol), 4,4'-thiobis-(6-t-butyl-o-cresol), 4,6-bis(octylthiomethyl)-o-cresol
[0113] Examples of sulfur-containing phenolic antioxidants include 2,4-bis(octylthiomethyl)-6-methylphenol, 4-[[4,6-bis(octylthio)-1,3,5-triazin-2-yl]amino]-2,6-di-t-butylphenol (also known as 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol). As sulfur-free phenolic antioxidants, 2,6-di-t-butyl-4-methylphenol and octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate are preferred, and as sulfur-containing phenolic antioxidants, 4,6-bis(octylthiomethyl)-o-cresol and 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol are preferred. These can be used alone or in combination of two or more in any ratio. Sulfur-containing phenolic antioxidants and sulfur-free phenolic antioxidants can also be used in combination.
[0044] Examples of organic phosphorus antioxidants include triphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, 4,4'-butylidene-bis(3-methyl-6-t-butylphenyl ditridecyl) phosphite, 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane (also known as cyclic neopentane tetrayl bis(octadecyl phosphite)), tris(nonylphenyl phosphite), tris(mono(or di)nonylphenyl) phosphite, diisodecyl pentaerythritol diphosphite, tris(2,4-di-t-butylphenyl) phosphite, cyclic neopentane tetrayl phosphite-based antioxidants such as rubis(2,4-di-t-butylphenyl)phosphite, cyclic neopentanetetraylbis(2,6-di-t-butyl-4-methylphenyl)phosphite, and 2,2-methylenebis(4,6-di-t-butylphenyl)octylphosphite; and antioxidants having a phosphaphenanthrene ring such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(3,5-di-t-butyl-4-hydroxybenzyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-decyloxy-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. Phosphite-based antioxidants are preferred, and from the viewpoint of improving pressability, phosphite-based antioxidants having a long-chain alkyl (e.g., carbon atom number 9 or more) are more preferred. Examples thereof include diphenylisodecylphosphite, phenyldiisodecylphosphite, 4,4'-butylidene-bis(3-methyl-6-t-butylphenylditridecyl)phosphite, 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, tris(nonylphenylphosphite), tris(mono(or di)nonylphenyl)phosphite, and diisodecylpentaerythritol diphosphite.
[0045] Examples of the amine-based antiaging agents include bis(4-t-butylphenyl)amine, poly(2,2,4-trimethyl-1,2-dihydroquinoline), 6-ethoxy-1,2-dihydro-2,2,4-trimethylquinoline, reaction products of diphenylamine and acetone, 1-(N-phenylamino)-naphthalene, diphenylamine derivatives, dialkyldiphenylamines, N,N'-diphenyl-p-phenylenediamine, mixed diallyl-p-phenylenediamine, N-phenyl-N'-isopropyl-p-phenylenediamine, and N,N'-di-2-naphthyl-p-phenylenediamine compounds.
[0046] Examples of quinone-based antiaging agents include hydroquinone compounds such as 2,5-di-t-butylhydroquinone, 2,5-di-t-octylhydroquinone, 2,6-di-n-dodecylhydroquinone, 2-n-dodecyl-5-chlorohydroquinone, and 2-t-octyl-5-methylhydroquinone.
[0047] Examples of the sulfur-based antioxidant include dilauryl-3,3'-thiodipropionate and distearyl-3,3'-tridipropionate.
[0048] Examples of the phenothiazine-based antioxidants include phenothiazine, 10-methylphenothiazine, 2-methylphenothiazine, and 2-trifluoromethylphenothiazine.
[0049] <Organic solvent> The binder composition for an all-solid-state secondary battery of the present invention contains an organic solvent. Examples of the organic solvent include aromatic hydrocarbons such as toluene and xylene; ethers such as cyclopentyl methyl ether; and esters such as butyl acetate and butyl butyrate, with butyl butyrate and xylene being preferred. The organic solvent may be one type or a combination of two or more types in any ratio.
[0050] When the (meth)acrylic polymer is obtained as an aqueous dispersion, the solvent of the aqueous dispersion can be exchanged with the organic solvent. The method of solvent exchange is not particularly limited, and includes a method of placing the aqueous dispersion and the organic solvent in a rotary evaporator, reducing pressure and performing solvent exchange and dehydration at a predetermined temperature.
[0051] <Other ingredients> In addition to the above components, the binder composition for all-solid-state secondary batteries of the present invention may contain components such as leveling agents, reinforcing materials, antifoaming agents, antiaging agents, surfactants, and dispersants. These components can be known. In addition, as long as the effects of the present invention are not impaired, binders other than (meth)acrylic polymers may be contained. For example, polymers containing monomer units selected from vinylidene fluoride (VDF) monomer units and hexafluoropropylene (HFP) monomer units (e.g., polyvinylidene fluoride (PVDF), poly(hexafluoropropylene) (PHFP), etc.), styrene-butadiene copolymers (SBR), acrylonitrile-butadiene copolymers (NBR), hydrogenated NBR, and polymers with a gel content of more than 50%.
[0052] <Composition and viscosity of binder composition> In the binder composition for all-solid-state secondary batteries of the present invention, it is important to use the antioxidant in an amount of 0.005 parts by mass or more and 0.5 parts by mass or less relative to 100 parts by mass of the polymer. The content of the antioxidant is preferably 0.0085 parts by mass or more, more preferably 0.01 parts by mass or more, from the viewpoint of improving the pressing property and improving the cycle characteristics, and is preferably 0.3 parts by mass or less, more preferably 0.2 parts by mass or less, from the viewpoint of the output characteristics. The antioxidant in the binder composition can be identified, for example, by high performance liquid chromatography / mass spectrometry, and in this case, fast atom bombardment (FAB) can be used. The amount of the antioxidant in the binder composition can be determined, for example, by a calibration curve method using high performance liquid chromatography. The solid content concentration of the binder composition is preferably 5% by mass or more, more preferably 6% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less.
[0053] The binder composition may have a viscosity (Brookfield B type viscometer, 60 rpm, 25° C.) of 2000 mPa·s or less, and preferably 1800 mPa·s or less. From the viewpoint of stability over time, the viscosity is preferably 50 mPa·s or more, and more preferably 500 mPa·s or more.
[0054] <Method of preparing binder composition> The method for preparing the binder composition for an all-solid-state secondary battery of the present invention is not particularly limited, and examples thereof include a method in which the above-mentioned (meth)acrylic polymer, antioxidant, and any other components are mixed in an organic solvent. When the (meth)acrylic polymer is obtained as an aqueous dispersion, the solvent of the aqueous dispersion is exchanged with the organic solvent, and the anti-aging agent and other components are mixed before or after the solvent exchange to obtain a binder composition. The method of solvent exchange is not particularly limited, and includes a method of putting the aqueous dispersion and the organic solvent in a rotary evaporator, reducing the pressure and performing the solvent exchange and dehydration at a predetermined temperature. The timing of mixing the anti-aging agent is not particularly limited, and may be either before or after the organic solvent exchange. In order to adjust the concentration of the binder composition, an organic solvent may be further added after the solvent exchange.
[0055] (Slurry composition for solid electrolyte layer of all-solid-state secondary battery) The slurry composition for a solid electrolyte layer of an all-solid-state secondary battery of the present invention (hereinafter also referred to as "slurry composition for a solid electrolyte layer") contains the above-mentioned binder composition for an all-solid-state secondary battery and a solid electrolyte.
[0056] <Solid electrolyte> The solid electrolyte is not particularly limited as long as it has the conductivity of charge carriers such as lithium ions, and examples of the solid electrolyte include inorganic solid electrolytes and polymer inorganic solid electrolytes. The solid electrolyte may be one type or a combination of two or more types in any ratio, and may be a mixture of an inorganic solid electrolyte and a polymer inorganic solid electrolyte.
[0057] <<Inorganic solid electrolyte>> The inorganic solid electrolyte is not particularly limited, and examples thereof include crystalline inorganic ion conductors and amorphous inorganic ion conductors. For example, when the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery, the inorganic solid electrolyte is preferably a crystalline inorganic lithium ion conductor or an amorphous inorganic lithium ion conductor.
[0058] Hereinafter, a case will be described in which the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery as an example, but the present invention is not limited to this case. Crystalline inorganic lithium ion conductors include Li3N, LISICON (Li 14 Zn(GeO4)4), perovskite-type Li 0.5 La 0.5 TiO3, garnet type Li7La3Zr2O 10 , LIPON (Li 3+y PO 4-x N x ), Thio-LISICON (Li 3.75 Ge 0.25 P 0.75 S4) and the like. Examples of amorphous inorganic lithium ion conductors include glass Li-Si-SO and Li-PS.
[0059] Among these, from the viewpoint of the electrical conductivity of the inorganic solid electrolyte, an amorphous inorganic lithium ion conductor is preferred, and an amorphous sulfide containing Li and P is more preferred because it has high lithium ion conductivity and can reduce internal resistance.
[0060] The amorphous sulfide containing Li and P is more preferably a sulfide glass made of Li2S and P2S5 from the viewpoint of reducing the internal resistance of the battery and improving the output characteristics, and particularly preferably a sulfide glass made from a mixed raw material of Li2S and P2S5 having a molar ratio of Li2S:P2S5 of 65:35 to 85:15. Sulfide glass ceramics obtained by reacting such a mixed raw material by a mechanochemical method can also be suitably used. From the viewpoint of maintaining a high lithium ion conductivity, the mixed raw material preferably has a molar ratio of Li2S:P2S5 of 68:32 to 80:20.
[0061] The lithium ion conductivity of the inorganic solid electrolyte is not particularly limited and is not more than 1×10 -4 S / cm or more is preferable, and 1×10 -3 More preferably, it is S / cm or more.
[0062] The amorphous sulfide inorganic solid electrolyte containing Li and P can contain at least one sulfide selected from the group consisting of Al2S3, B2S3 and SiS2 as a starting material in addition to the above Li2S and P2S5 to the extent that the ion conductivity is not reduced. This can stabilize the glass component in the inorganic solid electrolyte. Similarly, the inorganic solid electrolyte may contain at least one lithium ortho-oxo acid selected from the group consisting of Li3PO4, Li4SiO4, Li4GeO4, Li3BO3, and Li3AlO3, in addition to Li2S and P2S5, which can stabilize the glass component in the inorganic solid electrolyte.
[0063] The number-average particle size of the inorganic solid electrolyte is preferably 0.1 μm or more, more preferably 0.3 μm or more, and is preferably 20 μm or less, more preferably 10 μm or less, even more preferably 7 μm or less, and particularly preferably 5 μm or less. If it is equal to or greater than the lower limit, handling is easy and the adhesion of the layer formed using the slurry composition can be sufficiently improved. On the other hand, if it is equal to or less than the upper limit, the surface area of the inorganic solid electrolyte can be sufficiently secured, and the output characteristics of the all-solid-state secondary battery can be sufficiently improved. In this specification, the "number average particle size" of the inorganic solid electrolyte can be determined by observing 100 inorganic solid electrolyte particles with an electron microscope, measuring the particle size according to JIS Z8827-1:2008, and calculating the average value.
[0064] <<Polymer inorganic solid electrolyte>> Examples of polymeric inorganic solid electrolytes include polyethylene oxide derivatives and polymers containing polyethylene oxide derivatives, polypropylene oxide derivatives and polymers containing polypropylene oxide derivatives, phosphate polymers, and polycarbonate derivatives and polymers containing polycarbonate derivatives, which contain an electrolyte salt.
[0065] When the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery, the electrolyte salt is not particularly limited, and examples thereof include fluorine-containing lithium salts such as lithium hexafluorophosphate (LiPF), lithium tetrafluoroborate (LiBF), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0066] <Other ingredients> The slurry composition for a solid electrolyte layer may contain, in addition to the above components, components such as a leveling agent, a reinforcing agent, a defoaming agent, an antiaging agent, etc. As these components, known ones may be used. The slurry composition for the solid electrolyte layer may contain an organic solvent optionally added during preparation of the slurry composition, and the organic solvents mentioned for the binder composition may be used as the added solvent. Specifically, butyl butyrate and xylene are preferred solvents.
[0067] <Composition and viscosity of slurry composition for solid electrolyte layer> The amount of the binder composition contained in the slurry composition for a solid electrolyte layer is preferably such that the (meth)acrylic polymer in the binder composition is 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 7 parts by mass or less, more preferably 5 parts by mass or less, per 100 parts by mass of the solid electrolyte.
[0068] The viscosity of the slurry composition for the solid electrolyte layer (Brookfield B type viscometer, 60 rpm, 25° C.) is preferably 500 mPa·s or more, more preferably 1000 mPa·s or more, and is preferably 10000 mPa·s or less, more preferably 6000 mPa·s or less.
[0069] <Method for preparing slurry composition for solid electrolyte layer> The method for preparing the slurry composition for the solid electrolyte layer is not particularly limited, and examples thereof include a method of mixing the above-mentioned binder composition, solid electrolyte, any additional organic solvent, and any other components.
[0070] (Slurry composition for electrodes of all-solid secondary batteries) The slurry composition for an all-solid-state secondary battery electrode of the present invention (hereinafter also referred to as "slurry composition for an electrode") contains the above-mentioned all-solid-state secondary battery binder composition, a solid electrolyte, and an electrode active material.
[0071] <Solid electrolyte> For the solid electrolyte, the description in the above-mentioned slurry composition for solid electrolyte layer is applied, and those exemplified or preferred examples in the description can be used.
[0072] <Electrode active material> The electrode active material is a material that transfers electrons at the electrode of an all-solid-state secondary battery. When the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery, a material that can absorb and release lithium is usually used as the electrode active material. Hereinafter, a case will be described in which the all-solid-state secondary battery is an all-solid-state lithium ion secondary battery, but the present invention is not limited thereto.
[0073] The positive electrode active material is not particularly limited, and examples thereof include a positive electrode active material made of an inorganic compound and a positive electrode active material made of an organic compound. The positive electrode active material may be one type or a combination of two or more types in any ratio, and may be a mixture of an inorganic compound and an organic compound.
[0074] Examples of the positive electrode active material made of an inorganic compound include transition metal oxides, composite oxides of lithium and transition metals (lithium-containing composite metal oxides), transition metal sulfides, etc. Examples of the transition metals include Fe, Co, Ni, Mn, etc. Examples of the inorganic compounds used in the positive electrode active material include lithium-containing composite metal oxides such as Co-Ni-Mn (Li(Co Mn Ni)O2), Ni-Co-Al lithium-containing composite metal oxides, lithium-containing cobalt oxide (LiCoO2), lithium-containing nickel oxide (LiNiO2), lithium manganate (LiMnO2, LiMn2O4), olivine-type lithium iron phosphate (LiFePO4), and LiFeVO4; transition metal sulfides such as TiS2, TiS3, and amorphous MoS2; Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, and V6O 13 and the like. These compounds may be partially element-substituted.
[0075] Examples of the positive electrode active material made of an organic compound include polyaniline, polypyrrole, polyacene, disulfide-based compounds, polysulfide-based compounds, and N-fluoropyridinium salts.
[0076] Examples of the negative electrode active material include carbon allotropes such as graphite and coke. The negative electrode active material made of a carbon allotrope can be in the form of a mixture or coating with a metal, metal salt, oxide, etc. Examples of the negative electrode active material include oxides or sulfates of silicon, tin, zinc, manganese, iron, nickel, etc.; metallic lithium; lithium alloys such as Li-Al, Li-Bi-Cd, and Li-Sn-Cd; lithium transition metal nitrides; silicone; and the like.
[0077] The number-average particle diameter of the electrode active material is preferably 0.1 μm or more, more preferably 1 μm or more, and is preferably 40 μm or less, more preferably 30 μm or less. If it is equal to or greater than the lower limit, handling is easy and the adhesiveness of the resulting electrode mixture layer can be sufficiently improved. On the other hand, if it is equal to or less than the upper limit, the surface area of the electrode active material can be sufficiently secured, and the output characteristics of the all-solid-state secondary battery can be sufficiently improved. In this specification, the "number average particle size" of the electrode active material can be determined by observing 100 particles of the electrode active material under an electron microscope, measuring the particle size according to JIS Z8827-1:2008, and calculating the average value.
[0078] <Conductive material> The electrode slurry composition may contain a conductive material. By containing a conductive material, it is possible to easily ensure electrical contact between electrode active materials in the electrode mixture layer. Examples of the conductive material include carbon black (e.g., acetylene black, Ketjen Black (registered trademark), furnace black, etc.), single-layer or multi-layer carbon nanotubes (multi-layer carbon nanotubes include cup-stack type), carbon nanohorns, vapor-grown carbon fibers, milled carbon fibers obtained by crushing polymer fibers after firing, single-layer or multi-layer graphene, conductive carbon materials such as carbon nonwoven fabric sheets obtained by firing nonwoven fabrics made of polymer fibers, and fibers or foils of various metals. Among them, acetylene black, Ketjen Black, and furnace black are preferred. The conductive material may be one type or a combination of two or more types in any ratio.
[0079] <Other ingredients> In addition to the above components, the electrode slurry composition may contain other components such as a leveling agent, a reinforcing agent, a defoaming agent, a surfactant, a dispersant, etc. Known components may be used. The electrode slurry composition may contain an organic solvent added at the time of preparation of the slurry composition, and the organic solvents mentioned for the binder composition may be used as the added solvent. Specifically, butyl butyrate and xylene are preferred solvents.
[0080] <Composition and viscosity of electrode slurry composition> The amount of solid electrolyte contained in the electrode slurry composition is preferably such that the ratio of the solid electrolyte to the total amount (100 mass%) of the electrode active material and the solid electrolyte is 10 mass% or more, more preferably 20 mass% or more, and also preferably 70 mass% or less, more preferably 60 mass% or less. If it is equal to or more than the lower limit, the ion conductivity can be sufficiently ensured, the electrode active material can be effectively utilized, and the capacity of the all-solid-state secondary battery can be sufficiently increased. If it is equal to or less than the upper limit, the amount of the electrode active material can be sufficiently ensured, and the capacity of the all-solid-state secondary battery can be sufficiently increased.
[0081] The amount of the binder composition contained in the slurry composition for an electrode is preferably such that the (meth)acrylic polymer in the binder composition is 0.1 part by mass or more, more preferably 0.5 parts by mass or more, and is preferably 7 parts by mass or less, more preferably 5 parts by mass or less, per 100 parts by mass of the combined amount of the electrode active material and the solid electrolyte.
[0082] The viscosity of the electrode slurry composition (Brookfield B type viscometer, 60 rpm, 25° C.) is preferably 500 mPa·s or more, more preferably 1000 mPa·s or more, and is preferably 10000 mPa·s or less, more preferably 6000 mPa·s or less.
[0083] <Method of preparing a slurry composition for electrodes> The method for preparing the slurry composition is not particularly limited, and examples thereof include a method of mixing the above-mentioned binder composition, solid electrolyte, electrode active material, any conductive material, any additional organic solvent, and any other components. When a conductive material is used, the binder composition and the conductive material may be mixed in advance, and the solid electrolyte, electrode active material, etc. may be added thereto.
[0084] (Solid electrolyte layer for all-solid-state secondary batteries) The solid electrolyte layer for an all-solid-state secondary battery of the present invention (hereinafter also referred to as "solid electrolyte layer") is formed using the slurry composition for a solid electrolyte layer for an all-solid-state secondary battery of the present invention, and can be obtained, for example, by applying the slurry composition for a solid electrolyte layer to the surface of a suitable substrate to form a coating film, and then drying the formed coating film.
[0085] The solid electrolyte layer of the present invention contains at least a solid electrolyte, a (meth)acrylic polymer and an antioxidant, and the content ratio of these components is usually equal to the content ratio in the slurry composition for the solid electrolyte layer.
[0086] The solid electrolyte layer can be formed, for example, by the following method. 1) A method of applying the slurry composition for a solid electrolyte layer of the present invention onto an electrode (usually the surface of an electrode mixture layer; the same applies below) and then drying it to form a solid electrolyte layer on an electrode; 2) A method for forming a solid electrolyte layer on an electrode by applying the slurry composition for a solid electrolyte layer of the present invention onto a substrate, drying the composition, and then transferring the resulting solid electrolyte layer onto an electrode; and 3) A method for forming a self-supporting solid electrolyte layer by applying the slurry composition for a solid electrolyte layer of the present invention onto a substrate, drying the slurry composition for a solid electrolyte layer obtained by pulverizing the dried product into a powder, and then forming the powder into a layer.
[0087] The methods of application, drying, transfer, pulverization, molding, and the like used in the above methods 1) to 3) are not particularly limited, and known methods can be used.
[0088] For example, examples of the coating method include a doctor blade method, a dip method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, and a brush coating method.
[0089] For example, drying methods include drying with warm air, hot air or low humidity air, vacuum drying, and drying by irradiation with (far) infrared rays or electron beams, etc. Drying conditions can be appropriately set, and the drying temperature is preferably 50° C. or higher and 250° C. or lower, and more preferably 80° C. or higher and 200° C. or lower. The drying time is not particularly limited, and is usually performed within a range of 10 minutes to 60 minutes.
[0090] The solid electrolyte layer may be stabilized by pressing the dried solid electrolyte layer. The pressing method is not particularly limited, and examples of the pressing method include die pressing and calendar pressing.
[0091] The amount of the solid electrolyte layer slurry composition to be applied is not particularly limited, and can be appropriately set depending on the desired thickness of the electrode mixture layer, etc. The thickness of the solid electrolyte layer is not particularly limited, and is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, and is preferably 1000 μm or less, more preferably 800 μm or less, and even more preferably 600 μm or less. If it is above the lower limit, short circuit between the positive electrode and the negative electrode can be sufficiently prevented, and if it is below the lower limit, it is advantageous in terms of lowering the internal resistance.
[0092] (Electrode for all-solid-state secondary battery) The electrode for an all-solid-state secondary battery of the present invention (hereinafter also referred to as "electrode") is formed using the slurry composition for an all-solid-state secondary battery electrode of the present invention. For example, the slurry composition for an electrode is applied to the surface of a current collector to form a coating film, and then the formed coating film is dried to obtain an electrode comprising a current collector and an electrode mixture layer on the current collector.
[0093] The electrode of the present invention contains at least a solid electrolyte, an electrode active material, a (meth)acrylic polymer and an antioxidant, and the content ratios of these components are usually equal to the content ratios in the electrode slurry composition.
[0094] The current collector is not particularly limited as long as it is a material that has electrical conductivity and is electrochemically durable. From the viewpoint of heat resistance, metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, and platinum are preferred, and among them, aluminum is particularly preferred for the positive electrode, and copper is particularly preferred for the negative electrode. The shape of the current collector is not particularly limited, and a sheet-like one with a thickness of about 0.001 mm to 0.5 mm is preferred. The current collector is preferably roughened in advance before use in order to increase the adhesive strength with the electrode mixture layer. The roughening method is not particularly limited, and examples thereof include mechanical polishing, electrolytic polishing, and chemical polishing. In the mechanical polishing method, abrasive cloth paper to which abrasive particles are fixed, grinding stone, emery buff, wire brush equipped with steel wire, etc., are used. In addition, an intermediate layer may be formed on the surface of the current collector in order to increase the adhesive strength and electrical conductivity between the current collector and the electrode mixture layer.
[0095] The method for applying the slurry composition for an electrode is not particularly limited, and the methods mentioned for applying the slurry composition for a solid electrolyte layer can be used. The method for drying the slurry composition for an electrode is not particularly limited, and the methods mentioned for drying the slurry composition for a solid electrolyte layer can be used. The electrode may be stabilized by pressing the dried electrode. The pressing method is not particularly limited, and examples thereof include die pressing and calendar pressing.
[0096] The amount of the electrode slurry composition to be applied is not particularly limited, and can be appropriately set depending on the desired thickness of the electrode mixture layer, etc. The weight of the electrode mixture layer is not particularly limited and may be up to 1.0 mg / cm 2 More preferably, it is 5.0 mg / cm or more. 2 or more, and 30.0 mg / cm 2Less than 25.0 mg / cm is preferred. 2 The following is more preferred:
[0097] (All-solid-state secondary battery) The all-solid-state secondary battery of the present invention includes at least one of the solid electrolyte layer and electrodes (positive electrode, negative electrode) of the present invention. That is, in the all-solid-state secondary battery of the present invention, at least one of the solid electrolyte layer, the positive electrode, and the negative electrode is formed using a slurry composition containing the binder composition of the present invention (in the case of the solid electrolyte layer, it is a slurry composition for the solid electrolyte layer, and in the case of the positive electrode or the negative electrode, it is a slurry composition for the electrode).
[0098] Here, the electrode that can be used in the all-solid-state secondary battery of the present invention and does not fall under the electrode of the present invention is not particularly limited, and any electrode for an all-solid-state secondary battery can be used.
[0099] In addition, the solid electrolyte layer that can be used in the all-solid-state secondary battery of the present invention and does not fall under the solid electrolyte layer of the present invention is not particularly limited, and any solid electrolyte layer can be used.
[0100] The all-solid-state secondary battery of the present invention can be obtained by laminating a positive electrode and a negative electrode so that the positive electrode composite layer of the positive electrode and the negative electrode composite layer of the negative electrode face each other via a solid electrolyte layer, optionally applying pressure to obtain a laminate, and then placing the laminate in a battery container as is or after rolling or folding, etc., depending on the shape of the battery, and sealing the battery. If necessary, an expand metal, a fuse, an overcurrent prevention element such as a PTC element, a lead plate, etc. can be placed in the battery container to prevent pressure rise inside the battery and overcharging and discharging. The shape of the battery is not particularly limited, and examples thereof include coin type, button type, sheet type, cylindrical type, square type, flat type, etc.
[0101] In the manufacture of an all-solid-state secondary battery, press working is usually performed in any of the manufacturing steps of the all-solid-state secondary battery, such as the stage of forming the solid electrolyte layer or the electrode mixture layer, the stage of laminating each layer, the stage of assembling the battery cell, etc. This press working is generally performed at a pressure of 50 MPa or more and 1500 MPa or less, but by using the binder composition of the present invention, excellent pressability is imparted to the layers (solid electrolyte layer, electrode mixture layer) to be formed, so that it becomes possible to realize excellent output characteristics and high-temperature cycle characteristics in the all-solid-state secondary battery. EXAMPLES
[0102] The present invention will be specifically described below based on examples, but the present invention is not limited thereto. In the following, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In the examples and comparative examples, the weight average molecular weight of the polymer, the content ratio of the monomer unit, and the gel amount were measured as follows. The leveling property and adhesion (peel strength) of the slurry composition, and the battery characteristics (output characteristics, high temperature cycle characteristics) of the all-solid-state secondary battery were evaluated as follows.
[0103] <Weight average molecular weight in polymer> The weight average molecular weight of the polymer prepared in each Example and Comparative Example was calculated based on the polystyrene equivalent molecular weight obtained using high performance liquid chromatography (apparatus: Tosoh Corporation, model number "HLC8220"). For high performance liquid chromatography, three columns connected together (Showa Denko KK, model number "Shodex KF-404HQ", column temperature: 40°C, carrier: tetrahydrofuran with a flow rate of 0.35 ml / min) and a differential refractometer and an ultraviolet detector were used as detectors. The molecular weight was calibrated at 12 points using standard polystyrene (Polymer Laboratory Co., Ltd., standard molecular weight: 500 to 3,000,000).
[0104] <Content of monomer units in polymer> 100 g of the binder composition prepared in Example 8 described later was solidified with 1 L of methanol, and then vacuum dried at a temperature of 60° C. for 12 hours. The obtained dried polymer was1 The results were analyzed by H-NMR. Based on the analytical values obtained, the content ratio (mass%) of each monomer unit and structural unit contained in the polymer in the binder composition was calculated. The content ratio of the monomer unit in other examples and comparative examples is substantially the same as the content ratio (charged amount) of each monomer in the monomer composition.
[0105] <Gel amount (THF insoluble amount)> In the preparation of the binder composition of each Example and Comparative Example, the reaction liquid before mixing with the antiaging agent after polymerization of the monomer (for Example 8, the aqueous dispersion before mixing with the antiaging agent after concentration after hydrogenation reaction) was dried under an environment of 50% humidity and 23°C to 25°C to prepare a film with a thickness of 3±0.3 mm. The prepared film was cut into 5 mm squares to prepare a plurality of film pieces, and these film pieces were precisely weighed to about 1 g. The weight of the precisely weighed film piece was defined as W0. Next, the precisely weighed film piece was immersed in 100 g of tetrahydrofuran (THF) at 25°C for 24 hours. Thereafter, the film piece was pulled out from the THF, and the pulled out film piece was vacuum dried at 105°C for 3 hours, and its weight (weight of the insoluble portion) W1 was measured. Then, the THF insoluble portion was calculated according to the following formula, and was defined as the gel amount (mass%). Gel amount (mass%) = W1 / W0 x 100
[0106] <Leveling ability> A flat-bottomed cylindrical transparent glass tube with an inner diameter of 30 mm and a height of 120 mm was prepared, and two marked lines were made at positions 55 mm and 85 mm above the bottom of the tube (hereinafter, the marked line at the height of 55 mm will be referred to as "line A", and the marked line at the height of 85 mm will be referred to as "line B"). The slurry compositions obtained in the Examples and Comparative Examples were filled into the glass tubes up to line A, and the tubes were sealed with rubber stoppers and then left in an upright position in a 25° C. environment for 10 minutes. Thereafter, the time t from when the glass tube was laid horizontally until the tip of the liquid surface of the slurry composition passed line B was measured, and the leveling property was evaluated according to the following criteria: The shorter the time t, the better the leveling property during coating. A: Time t is less than 1 second B: Time t is 1 second or more and less than 5 seconds C: Time t is 5 seconds or more and less than 10 seconds D: Time t is 10 seconds or more
[0107] <Adhesion (peel strength)> The copper foils provided with the electrodes or solid electrolyte layers obtained in the Examples and Comparative Examples were cut into rectangles measuring 2.5 cm wide and 10 cm long to prepare test pieces, and cellophane tape was attached to the surface of the electrode composite layer or solid electrolyte layer of the test piece. The stress was measured when the cellophane tape was peeled off from one end of the test piece in a 180° direction at a speed of 50 mm / min. The measurement was carried out 10 times, and the average value was calculated, which was designated as the peel strength (N / m), and the adhesion was evaluated according to the following criteria. A higher average peel strength value indicates better adhesion. A: Average peel strength is 20N / m or more B: Average peel strength is 15N / m or more and less than 20N / m C: Average peel strength is 10N / m or more and less than 15N / m D: Average peel strength is less than 10N / m
[0108] <Battery characteristics: Output characteristics> The all-solid-state secondary batteries prepared in the examples and comparative examples were charged to 4.3 V by a constant current method of 0.1 C, and then discharged to 3.0 V at 0.1 C to determine the 0.1 C discharge capacity. Then, they were charged to 4.3 V at 0.1 C, and then discharged to 3.0 V at 10 C to determine the 10 C discharge capacity. The same measurements were taken for 10 cells, and the average of the 0.1C discharge capacity was taken as 0.1C discharge capacity a, and the average of the 10C discharge capacity was taken as 10C discharge capacity b. The capacity ratio, expressed as the ratio of the 10C discharge capacity b to the 0.1C discharge capacity a (b / a (%)), was calculated and evaluated according to the following criteria. The larger this value, the smaller the internal resistance and the better the output characteristics. A: Capacity ratio 50% or more B: Capacity ratio 40% or more and less than 50% C: Capacity ratio 30% or more and less than 40% D: Less than 30% capacity
[0109] <Battery characteristics: High temperature cycle characteristics> The all-solid-state secondary batteries produced in the Examples and Comparative Examples were charged at 60° C. from 3 V to 4.3 V at 0.1 C, and then discharged at 0.1 C from 4.3 V to 3 V, for 100 cycles. The capacity retention rate, which is expressed as the ratio (d / c (%)) of the 0.1 C discharge capacity d at the 100th cycle to the 0.1 C discharge capacity c at the 5th cycle, was determined and evaluated according to the following criteria. The larger this value, the smaller the discharge capacity loss and the more excellent the high-temperature cycle characteristics. A: Capacity retention rate of 60% or more B: Capacity retention rate: 50% to less than 60% C: Capacity retention rate: 40% to less than 50% D: Capacity retention rate: 30% to less than 40%
[0110] (Example 1: All-solid-state secondary battery having a negative electrode of the present invention) <Preparation of (meth)acrylic polymer and binder composition> Into a 1 L flask equipped with a stirrer and a septum, 100 parts of ion-exchanged water and 0.2 parts of sodium dodecylbenzenesulfonate as an emulsifier were added, the gas phase was replaced with nitrogen gas, and the temperature was raised to 60°C. After that, 0.25 parts of potassium persulfate (KPS) was dissolved in 20.0 parts of ion-exchanged water as a polymerization initiator and added. Meanwhile, in a separate container, 40 parts of ion-exchanged water, 1.0 part of sodium dodecylbenzenesulfonate as an emulsifier, 15 parts of styrene (St), 80 parts of n-butyl acrylate (BA), and 5 parts of acrylonitrile (AN) were mixed to obtain a monomer composition. This monomer composition was continuously added to the 1 L flask with a septum over a period of 3 hours to carry out polymerization. During the addition, the reaction was carried out at 60°C. After the addition was completed, the mixture was stirred at 80°C for an additional 3 hours to terminate the reaction. Next, 0.08 parts of octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (antiaging agent 1) and 0.02 parts of 4,6-bis(octylthiomethyl)-o-cresol (antiaging agent 2) were added as phenolic antioxidants per 100 parts of solids in the reaction liquid and mixed. Next, an appropriate amount of xylene was added to the obtained aqueous dispersion of the polymer to obtain a mixture, which was then distilled under reduced pressure at 80° C. to remove water and excess xylene from the mixture to obtain a binder composition (solid content: 8%).
[0111] <Preparation of Slurry Composition for Negative Electrode> 65 parts of graphite (number average particle diameter: 20 μm) as a negative electrode active material, 30 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle diameter: 0.9 μm) consisting of Li2S and P2S5 as a solid electrolyte, 3 parts of acetylene black as a conductive material, and the above binder composition (equivalent to 2 parts solid content) were mixed, and xylene was added to the resulting mixture to prepare a composition with a solid content concentration of 60%. This composition was mixed with a planetary mixer to obtain a slurry composition for a negative electrode composite layer. The leveling property was evaluated using the obtained slurry composition for a negative electrode.
[0112] <Preparation of negative electrode> The above-mentioned slurry composition for a negative electrode was applied to the surface of a copper foil as a current collector, and dried at 120° C. for 30 minutes to form a negative electrode mixture layer (basis weight: 10.0 mg / cm) on one side of the copper foil as a current collector. 2 The adhesion of the obtained negative electrode was evaluated.
[0113] <Preparation of Positive Electrode Slurry Composition> The positive electrode active material is a lithium composite oxide of Co-Ni-Mn, NMC532 (LiNi 5 / 10 Co 2 / 10 Mn 3 / 1065 parts of 10.0μm sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle diameter: 0.9μm) consisting of Li2S and P2S5 as a solid electrolyte, 3 parts of acetylene black as a conductive material, and a binder composition (for positive electrode composite layer) (equivalent to 2 parts solid content) prepared in the same manner as in Example 1 except that no antioxidant was added were mixed, and xylene was added to the resulting mixture to prepare a composition with a solid content concentration of 75%. This composition was mixed with a planetary mixer for 60 minutes, and then further adjusted to a solid content concentration of 70% with xylene, and then mixed with a planetary mixer for 10 minutes to obtain a positive electrode slurry composition.
[0114] <Preparation of positive electrode> The positive electrode slurry composition was applied to the surface of an aluminum foil as a current collector, and dried at 120° C. for 30 minutes to form a positive electrode mixture layer (basis weight: 18.0 mg / cm) on one side of the aluminum foil as a current collector. 2 ) was obtained.
[0115] <Preparation of Slurry Composition for Solid Electrolyte Layer> 98 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle size: 0.9μm) consisting of Li2S and P2S5 as a solid electrolyte was mixed with a binder composition (equivalent to 2 parts solid content) prepared in the same manner as in Example 1 except that no antioxidant was added, and xylene was added to the resulting mixture to prepare a composition with a solid content concentration of 60%. This composition was mixed with a planetary mixer to obtain a slurry composition for a solid electrolyte layer.
[0116] <Preparation of solid electrolyte layer> The slurry composition for the solid electrolyte layer was dried on a release sheet as a substrate, and the dried material peeled off from the release sheet was ground in a mortar to obtain a powder. 0.05 mg of the obtained powder was placed in a 10 mmφ mold and molded under a pressure of 200 MPa to obtain a pellet (solid electrolyte layer) with a thickness of 500 μm.
[0117] <Production of all-solid-state secondary batteries> The negative electrode and positive electrode obtained as described above were punched out to a diameter of 10 mm. The solid electrolyte layer obtained as described above was sandwiched between the punched positive electrode and negative electrode (at this time, the electrode mixture layer of each electrode was in contact with the solid electrolyte layer), and pressed at a pressure of 200 MPa to obtain a laminate for an all-solid-state secondary battery. The obtained laminate was placed in an evaluation cell (confining pressure: 40 MPa) to obtain an all-solid-state secondary battery. Then, the cell characteristics of the obtained all-solid-state secondary battery were evaluated.
[0118] In Examples 1 to 7, 9 to 12, and Comparative Examples 1 to 3, the binder composition, the slurry composition for the negative electrode composite layer, the slurry composition for the positive electrode composite layer, the slurry composition for the solid electrolyte layer, the negative electrode, the positive electrode, and the all-solid-state secondary battery were manufactured in the same manner as in Example 1, but the type and amount of each monomer in the monomer composition, and the type and amount of the antioxidant were the types and amounts shown in Table 1. The binder composition used in the slurry composition for the positive electrode composite layer and the slurry composition for the solid electrolyte layer was prepared in the same manner as the binder composition for the slurry composition for the negative electrode composite layer in each Example and Comparative Example, except that no antioxidant was added. The cell characteristics of the all-solid-state secondary battery produced were evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0119] The antioxidants in the table are as follows. Phenol-based antioxidant Antioxidant 1: Octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate Antioxidant 2: 4,6-bis(octylthiomethyl)-o-cresol Antioxidant 3: 4-[[4,6-bis(octylthio)-1,3,5-triazin-2-yl]amino]-2,6-di-t-butylphenol Antioxidant 4: 2,6-di-t-butyl-4-methylphenol Phosphite-based anti-aging agent Antioxidant 5: 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane
[0120] Example 8 A slurry composition for an anode, a slurry composition for a cathode, a slurry composition for a solid electrolyte layer, a solid electrolyte layer, an anode, a cathode and an all-solid-state secondary battery were produced in the same manner as in Example 1, except that a (meth)acrylic polymer was prepared as described below and a binder composition was obtained, and the cell characteristics of the battery were evaluated. The results are shown in Table 1. The method for measuring the content of the monomer unit in the (meth)acrylic polymer is as described above.
[0121] A reactor was charged with 2 parts of potassium oleate as an emulsifier, 0.1 parts of potassium phosphate as a stabilizer, and 150 parts of water, and further charged with 19 parts of acrylonitrile (AN), 48 parts of 1,3-butadiene (BD), 33 parts of butyl acrylate (BA), and 0.31 parts of t-dodecyl mercaptan as a molecular weight regulator, and emulsion polymerization was initiated at 10° C. in the presence of 0.015 parts of ferrous sulfate as an activator and 0.05 parts of paramenthane hydroperoxide as a polymerization initiator. When the polymerization conversion rate reached 85%, 0.2 parts of hydroxylamine sulfate per 100 parts of monomer was added to terminate the polymerization. After the polymerization was terminated, the mixture was heated and subjected to steam distillation under reduced pressure at 80° C. to recover the unreacted monomers, thereby obtaining an aqueous dispersion of the polymer.
[0122] 400mL of the aqueous dispersion of the obtained polymer (total solid content: 48g) was placed in a 1-liter autoclave equipped with a stirrer, and nitrogen gas was passed through for 10 minutes to remove dissolved oxygen in the aqueous dispersion. Then, 50mg of palladium acetate was dissolved in 180mL of water containing 4 times the molar amount of nitric acid relative to Pd as a hydrogenation reaction catalyst and added. After replacing the inside of the system with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3MPa, and hydrogenation reaction was carried out for 6 hours. The contents were returned to room temperature, the inside of the system was conditioned with nitrogen, and the contents were then concentrated using an evaporator until the solid concentration reached 40%, to obtain an aqueous dispersion of a (meth)acrylic polymer. Next, 0.08 parts of octadecyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (antiaging agent 1) and 0.02 parts of 4,6-bis(octylthiomethyl)-o-cresol (antiaging agent 2) as phenolic antioxidants were added to and mixed with this aqueous dispersion of the (meth)acrylic polymer per 100 parts of solids in the aqueous dispersion. Next, an appropriate amount of xylene was added to the aqueous dispersion containing the antioxidant to obtain a mixture. After that, water and excess xylene were removed from the mixture by vacuum distillation at 90°C to obtain a binder composition (solid content: 8%).
[0123] (Example 13) A positive electrode slurry composition containing the binder composition of the present invention was prepared, and a positive electrode including a positive electrode mixture layer formed using this slurry composition was fabricated.
[0124] <Preparation of Positive Electrode Slurry Composition> Next, we used the lithium composite oxide NMC532 (LiNi 5 / 10 Co 2 / 10 Mn 3 / 10 65 parts of 10.0 μm of Li2S and P2S5 sulfide glass (Li2S / P2S5=70 mol% / 30 mol%, number average particle diameter: 0.9 μm) as a solid electrolyte, 3 parts of acetylene black as a conductive material, and the binder composition (equivalent to 2 parts of solid content) prepared in Example 1 were mixed, and xylene was added to the resulting mixture to prepare a composition with a solid content concentration of 75%. This composition was mixed for 60 minutes with a planetary mixer, and further adjusted to a solid content concentration of 70% with xylene, and then mixed for 10 minutes with a planetary mixer to obtain a slurry composition for a positive electrode. The leveling property was evaluated using the obtained slurry composition for a positive electrode.
[0125] <Preparation of positive electrode> The positive electrode slurry composition was applied to the surface of an aluminum foil as a current collector, and dried at 120° C. for 30 minutes to form a positive electrode mixture layer (basis weight: 18.0 mg / cm) on one side of the aluminum foil as a current collector. 2The adhesion of the obtained positive electrode was evaluated.
[0126] Example 14 A slurry composition for a solid electrolyte layer containing the binder composition of the present invention was prepared.
[0127] <Preparation of Slurry Composition for Solid Electrolyte Layer> 98 parts of sulfide glass (Li2S / P2S5=70mol% / 30mol%, number average particle size: 0.9μm) consisting of Li2S and P2S5 as a solid electrolyte was mixed with the binder composition (equivalent to 2 parts solid content) prepared in Example 1, and xylene was added to the resulting mixture to prepare a composition with a solid content concentration of 60%. This composition was mixed with a planetary mixer to obtain a slurry composition for a solid electrolyte layer. The leveling property was evaluated using the obtained slurry composition for a solid electrolyte layer.
[0128] <Preparation of solid electrolyte layer> The solid electrolyte layer slurry composition was applied to a copper foil and dried for 30 minutes at 120° C. to obtain a solid electrolyte layer having a thickness of 100 μm on the copper foil. The adhesion was evaluated using the obtained solid electrolyte layer on the copper foil.
[0129] [Table 1]
[0130] As shown in Examples 1 to 12, it was confirmed that the negative electrode slurry composition using the binder composition for all-solid-state secondary batteries of the present invention has excellent leveling properties and adhesion, and that the use of this composition makes it possible to obtain an all-solid-state secondary battery having excellent output characteristics and high-temperature cycle characteristics. It was also confirmed in Examples 13 and 14 that the excellent leveling properties and adhesion properties can be obtained when the binder composition for all-solid-state secondary batteries of the present invention is used in the slurry composition for the positive electrode and the slurry composition for the solid electrolyte layer. In Comparative Example 1, in which a binder composition containing no antioxidant was used, the obtained all-solid-state secondary battery was inferior in output characteristics and high-temperature cycle characteristics. In Comparative Examples 2 and 3, an antioxidant was used, but the binder was outside the range of the present invention, and the leveling property and adhesion strength were poor. In addition, the obtained all-solid-state secondary batteries were poor in output characteristics and high-temperature cycle characteristics.
Claims
1. A binder composition for an all-solid-state secondary battery, comprising a polymer, an antioxidant, and an organic solvent, the polymer contains 32% by mass or more and 95% by mass or less of (meth)acrylic acid ester monomer units, 2% by mass or more and 30% by mass or less of α,β-unsaturated nitrile monomer units, and 3% by mass or more and 60% by mass or less of hydrophobic monomer units, and has a gel content of 50% by mass or less, The amount of the antioxidant is 0.005 parts by mass or more and 0.5 parts by mass or less relative to 100 parts by mass of the polymer. Binder composition for all-solid-state secondary batteries.
2. 2. The binder composition for an all-solid-state secondary battery according to claim 1, wherein the antioxidant is at least one selected from the group consisting of phenol-based antioxidants and organophosphorus-based antioxidants.
3. A slurry composition for a solid electrolyte layer of an all-solid-state secondary battery, comprising the binder composition for an all-solid-state secondary battery according to claim 1 or 2 and a solid electrolyte.
4. A slurry composition for an all-solid-state secondary battery electrode, comprising the binder composition for an all-solid-state secondary battery according to any one of claims 1 to 3, a solid electrolyte, and an electrode active material.
5. A solid electrolyte layer for an all-solid-state secondary battery, formed by using the slurry composition for a solid electrolyte layer for an all-solid-state secondary battery according to claim 3.
6. An electrode for an all-solid-state secondary battery, comprising an electrode mixture layer formed using the slurry composition for an all-solid-state secondary battery electrode according to claim 4.
7. An all-solid-state secondary battery comprising at least one of the solid electrolyte for an all-solid-state secondary battery according to claim 5 and the electrode for an all-solid-state secondary battery according to claim 6.
Citation Information
Patent Citations
Coating composition
JP1992114074A
All-solid secondary battery
JP2011054439A
All-solid type secondary battery
JP2013008611A
Composite particle for electrode for electrochemical element, electrode material for electrochemical element, electrode for electrochemical element, and electrochemical element
JP2013055049A
Binder composition for secondary battery positive electrode, slurry composition for secondary battery positive electrode, secondary battery positive electrode, and secondary battery
JP2013179040A